KMI LIBRARY WEB-SITE: PROSPEСTS OF DEVELOPMENT - Karaman, Tetiana (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
The article deals with questions of web-site organization of Kryvyi Rih Metallurgical Institute Library and highlights the prospects of new additional services, which appeared as a result of the newest information technologies.